The Role of Dienogest in the Short-Term Treatment of Endometriosis in Young Women - Arzoo, Shabera; Akter, Musammat Shamima; Begum, Nur Jahan; Jannat, Fatematul; Naher, Kamrun; Alam, Mohammed Badrul (Eastern Medical College Journal, 2025)
Background: Endometriosis is a long-term, benign, recurrent, debilitating disease experienced by women. Endometriosis associated pelvic pain (EAPP) is the most common complaint reported by patients with the condition. Nearly 70% of females with endometriosis present with EAPP while endometrioma are found in 17-44% of patients. The purpose of the study is to investigate the efficacy and safety of Dienogest as medical therapy to these patients. Materials and Methods: This prospective observational study was carried out in the department of Obstetrics & Gynecology of Eastern Medical College & Hospital from January to December 2023. A total of 96 patients with the age range of 15–35 years with complaints of pain and diagnosed as endometriosis by ultrasonogram were included. All the patients were treated by Dienogest 2 mg orally. The effects of treatment were determined by seeing the resolution of pain and decreasing the size of endometrioma. Patients were followed up in the 1st and 3rd months. Results: Out of 96 patients 72 reported their pain relief within 10-15 days after starting Dienogest. Out of 71 patients who had severe pain at enrollment only 3% had severe pain after 1 month and 1% had severe pain after 3 months of treatment with Dienogest. Successful reduction in endometriotic cyst size (>50%) was seen in 18 (18.75%) at the end of 1 month with Dienogest. At the end of 3 months 24 patients (25.0%) had significant cyst size reduction (>50%) with Dienogest. Complete disappearance of endometriomas was seen in 10 patients (10.41%). No major side effects after 3 months of treatment. Conclusion: Dienogest is a well-tolerated drug for endometriosis. It shows significant relief of pain. However, it was observed that the endometrioma did not grow further, but it did not show significant regression either. It is well tolerated with favorable safety profile. Eastern Med Coll J. July 2025; 10 (1): 45-50